2018
DOI: 10.21061/jte.v29i2.a.1
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Ask Me Why: Preschool Teachers’ Knowledge in Technology as a Determinant of Leadership Behavior

Abstract: In the Swedish preschool curriculum, technology education is emphasized as one of the most significant pedagogical areas. Particularly, the teacher's role is emphasized: It is the preschool teacher's responsibility to stimulate and challenge children's interest in science and technology. Unfortunately, prior research indicates that preschool teachers feel uncertain about what technology is and the extent of their knowledge on the topic. Based on the path-goal theory, this article will explore how preschool tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
(34 reference statements)
0
18
1
Order By: Relevance
“…It is clear from the differences between Figure 1 and Figure 2 that there is a gap in the participating preschool teachers' descriptions of technology and the practices involving technology with the children. In contrast to previous research (Öqvist & Högström, 2018), in their general description of technology the preschool teachers do not emphasise the application of artefacts as technology. However, these categories are prominent in the preschool activities.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…It is clear from the differences between Figure 1 and Figure 2 that there is a gap in the participating preschool teachers' descriptions of technology and the practices involving technology with the children. In contrast to previous research (Öqvist & Högström, 2018), in their general description of technology the preschool teachers do not emphasise the application of artefacts as technology. However, these categories are prominent in the preschool activities.…”
Section: Discussioncontrasting
confidence: 59%
“…If a different group of preschool teachers, including less technologically interested staff, had answered the questionnaire, the result may have been different. The reason for suggesting this is that earlier research has shown that, in general, preschool teachers' knowledge of technology is relatively limited and that they also are aware of that (Elvstrand et al, 2018;Öqvist, & Högström, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results regarding preschool teachers' apprehensions show a narrow view of technology as being related to computers and a more developed view as problem solving (Öqvist and Högström 2018) and that technology can be everything (Elvstrand et al 2018) and has been categorised in an overall system (Sundqvist 2016). However, the fact that preschool teachers have a developed view of technology does not necessarily mean that this is shared by the children.…”
Section: Previous Research On Technology Education In Preschoolmentioning
confidence: 99%
“…child minders or preschool teachers) interpret the concept of technology and the kind of activities that are related to it in the preschool setting (e.g. Elvstrand et al 2018;Sundqvist 2016;Sundqvist et al 2018;Öqvist and Högström 2018). This focus stems from the change in the Swedish preschool curriculum, as described above (The Swedish National Agency for Education 2016).…”
Section: Introductionmentioning
confidence: 99%